Health inequality implications from a qualitative study of experiences of poverty stigma in Scotland. (July 2019) - Inglis, Greig; McHardy, Fiona; Sosu, Edward; McAteer, John; Biggs, Hannah
Abstract: Rationale: Individuals living in Scotland's most deprived communities experience a higher burden of morbidity and early mortality than those living in more affluent areas. Experiences of poverty-based stigma may be one psychosocial mechanism through which socioeconomic position influences health, although there is little available data on this issue from a Scottish perspective. Objective: The aim of this study was to identify which aspects of poverty stigma are particularly salient to individuals with lived experience of poverty, and may therefore contribute to health inequalities. Methods: Five focus groups were conducted with 39 individuals with experience of living on low incomes in Scotland in order to explore their experiences and perceptions of poverty stigma. Results: Five main themes were identified, reflecting aspects of poverty stigma operating at various structural, public and individual levels: media representations of poverty; negative encounters with social security systems; perceived public attitudes regarding poverty in Scotland; lowered self-esteem and internalisation of negative attitudes, and; emotional responses to stigma. Conclusion: These dimensions of stigma potentially influence public health and health inequalities in Scotland, although future research will be necessary to quantify these and estimate their relationships with health outcomes. Highlights: Relatively little is currently known about poverty-based stigma in Scotland. People with experience of poverty discussed this issue in five focus groups. Participants' accounts reflected several forms of poverty stigma. Poverty stigma operates at various structural, social, and individual levels. Poverty stigma is a potentially important determinant of health inequalities.